COMPARISON OF ORAL CHLOROQUINE WITH SYSTEMIC MEGLUMINE ANTIMONIATE IN TREATMENT OF CUTANEOUS LEISHMANIASIS - Farooq, Muhammad; Farooq, Muhammad Saad; Bari, Arfan Ul; Malik, Tariq Mehmood (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the efficacy of oral chloroquine with systemic meglumine antimoniate in treatment of cutaneous leishmaniasis. Study Design: Open-label comparative prospective study. Place and Duration of Study: Study was conducted in the department of Dermatology, Combined Military Hospital Multan, from Jan to Oct 2018. Methodology: Fifty adult male patients completed the study. The inclusion criteria for the study were patients having untreated skin lesions less than 3 months old. Diagnosis was made on the basis of history and clinical features and was confirmed on histopathological examination. Patients were divided into 2 groups of 25 each, group A patients received meglumine antimoniate 810mg intramuscularly once a day whereas group B patients were given oral chloroquine 250mg twice a day. Pre-treatment complete physical examination was done along with blood complete picture, urine routine examination, liver function tests, renal function tests and electrocadiogram. They were repeated after 2 weeks and at the end of treatment. The efficacy was measured by healing of lesions with a measuring tape. Results: Fifty patients completed the study. At the end of treatment, among group A patients, 4 (16%) showed no improvement, 21 (84%) improved; whereas in group B patients, 11 (44%) showed no improvement, 14 (56%) showed improvement. Percentage reduction in surface area of skin lesions was 77.6% in group A, whereas in group B, it was 42.7%. Conclusion: Meglumine antimoniate showed better efficacy than chloroquine but oral chloroquine was also effective and can be used as an alternative therapy.